Argentina : Staff Report for 2022 Article IV Consultation and request for an Extended Arrangement under the Extended Fund-Facility-Press Release; Staff Report; and Staff Supplements. (IMF Staff Country Reports; Country Report, 2022)
Against the background of a decade of declining per-capita income and high inflation, the Article IV consultation focused on policies to begin to tackle Argentina's underlying impediments to sustained growth and low and stable inflation. Avoiding boom-bust dynamics suggests the need for greater emphasis on policies to promote net exports and mobilize domestic saving to finance much-needed investment. Reversing the high degree of financial dollarization, however, will take time and will require a durable commitment to tackle fiscal dominance and strengthen debt sustainability. Meanwhile, addressing budget rigidities is essential to improve Argentina's resilience to shocks, while reorienting public spending towards investment and innovation is critical to support productivity and reduce intergenerational inequities. Sustained political and social consensus is necessary for policy predictability and to balance demands from financing Argentina's large social welfare system while also encouraging private investment and formal employment.